Elegant Perfume Smelled Pen - Adham Juraev Menziya oglu; Ismoiljonova Ozoda Bekmurza qizi (Genius Publishing Group, 2022)
It is known that nowadays the demand for cheap, high-quality and healthy ballpoint pens is growing day by day, which plays an important role in the growth of human thinking and worldview. Currently, despite the diversity of entrepreneurs engaged in the sale of canned goods, the company plans to sell its ballpoint pens at low prices and improve human health.
Keywords: Pen; production; development; entrepreneurship